Diagnostic Characteristics of Pedagogical Experience on Development of Professional Competence of Physical Education Teachers - Shirinbekovich, Karaev Vokhid (European Journal of Life Safety and Stability (2660-9630), 2021)
The article presents the results of pedagogical research confirmed the validity of the proposed working task that the development of professional competence of teachers of physical education on the basis of the pedagogical model improves the quality of organizational training of professional activity in a secondary school. To study the level of development of the professional competence of physical education teachers at advanced training courses, we used such diagnostic methods as testing, questionnaires and experiment polls. In this case, a significant role was played by test B socio-psychological methods designed to identify and diagnose indicators of professional competence of physical culture teachers. These include methods that allowed to assess objectively the dominant motives of the teacher's pedagogical activity, readiness for self-education and also the level of formation of professional competence.